Control interno al departamento de bodega y su incidencia en el manejo del stock de inventarios de la empresa Agrotecban S.A. cantón Quevedo, - Macias Mendoza, Marisol Magdalena (2024)
The few internal administrative controls, inadequate objectives, deficient policies have caused a series of inconveniences that affect the operation of the company AGROTECBAN S.A. The personnel who work in the warehouse department are unaware of the policies that exist for the activities they carry out. The objective of this project is to determine the incidence of internal control in the Warehouse Department in the management of the inventory stock of the company AGROTECBAN S.A., in the Quevedo canton, period 2021-2022. The work was developed using descriptive research, with a quantitative and qualitative approach. Regarding its population and sample, it included a total of 10 participants, who belong to the company. The techniques used were the survey, the interview and direct observation, and the instrument used was the questionnaire. According to the results, in the comprehensive evaluation, challenges were identified in internal control, especially in the promotion of ethical values and risk management, pointing out the need for proactive strategies. Inventory management revealed critical areas in policies and information quality, suggesting the review of processes and the adoption of technologies. The financial analysis showed sustained growth and resilience. On the other hand, 80% of the participants indicated that the identification and mitigation of risks related to inventory management in the Warehouse Department is not carried out effectively. Concluding that it is essential to establish clear policies and procedures, in addition to promoting effective supervision, to ensure adequate compliance.